2013
DOI: 10.1038/nature12808
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial amelioration of inflammation and cell death after brain injury

Abstract: Traumatic brain injury (TBI) is increasingly appreciated to be highly prevalent and deleterious to neurological function 1, 2 . At present no effective treatment options are available, and little is known about the complex cellular response to TBI during its acute phase. To gain novel insights into TBI pathogenesis, we developed a novel closed-skull brain injury model that mirrors some pathological features associated with mild TBI in humans and used long-term intravital microscopy to study the dynamics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
506
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 480 publications
(541 citation statements)
references
References 24 publications
15
506
0
Order By: Relevance
“…This approach, although less efficient than direct parenchymal application, has been used previously to manipulate cortical function: [46][47][48] it is consistent with the notion that agents with molecular weights similar to the inhibitors used in our study undergo rapid transmeningeal diffusion into all layers of the cortex following topical epidural application, with a dilution factor of 1:100-500. [47][48][49] Such dilution could potentially explain why in our study epidural SC-560 treatment (at 500 mM) did not reduce resting CBF while previous studies noted decreased resting CBF and cerebral vasoconstriction following parenchymal superfusion of this inhibitor at concentrations !10 mM. 30,38,50 Because SC-560, as well naproxen, affected CBF only during the oligemic stage, it is also tempting to speculate that these COX inhibitors are more efficient in blocking the synthesis of vasoconstricting prostanoids that mediate the post-CSD oligemia than inhibiting the formation of vasodilating prostanoids that control basal CBF.…”
Section: Discussionsupporting
confidence: 89%
“…This approach, although less efficient than direct parenchymal application, has been used previously to manipulate cortical function: [46][47][48] it is consistent with the notion that agents with molecular weights similar to the inhibitors used in our study undergo rapid transmeningeal diffusion into all layers of the cortex following topical epidural application, with a dilution factor of 1:100-500. [47][48][49] Such dilution could potentially explain why in our study epidural SC-560 treatment (at 500 mM) did not reduce resting CBF while previous studies noted decreased resting CBF and cerebral vasoconstriction following parenchymal superfusion of this inhibitor at concentrations !10 mM. 30,38,50 Because SC-560, as well naproxen, affected CBF only during the oligemic stage, it is also tempting to speculate that these COX inhibitors are more efficient in blocking the synthesis of vasoconstricting prostanoids that mediate the post-CSD oligemia than inhibiting the formation of vasodilating prostanoids that control basal CBF.…”
Section: Discussionsupporting
confidence: 89%
“…Results: Immunohistochemical labeling demonstrated elevated expression of Iba-1 and GFAP in the cortex, corpus callosum, and hippocampus 2, 24 h, and 1week after HIFU exposure, suggesting a diffuse neuroinflammatory response. This is in agreement with previous reports [1, 3,4]. Animals subjected to HIFU exposure exhibited significantly poorer performance in the rotarod behavioral tests than those with a sham exposure up to 1 month postinjury, indicating a chronic functional impairment in locomotor ability.…”
Section: Pipeline Sessionsupporting
confidence: 93%
“…It is likely, therefore, that reducing neuroinflammation associated with pathology is not necessarily always of value. Roth et al (2014) investigated the role of purinergic signaling in neuroinflammatory responses following TBI and found that the P2X7-mediated inflammatory response contributes to better outcomes, with activated microglia protecting the parenchyma and myelomonocytic cells invading the damaged meninges. Both purinergic mechanisms and reactive oxygen species are key players in the response to injury.…”
Section: Purinergic Regulation Of Neuroinflammation In Cns Disordersmentioning
confidence: 99%